Proceedings of the International Conference on Agro-Biotechnology, Biosafety and Seed Systems in Developing Countries - Nampala, Paul; Makara, Arthur M. (Science Foundation for Livelihoods and Development, Kampala., 2011)
The Science Foundation for Livelihoods and Development (SCIFODE) and the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) thank all partners and individuals who provided support to the AGBIOSAFESEED2010 conference and the publication of proceedings thereof. We particularly thank the Uganda National Council for Science and Technology (UNCST); Program for Biosafety Systems (PBS); National Agricultural Research Organisation of Uganda (NARO); AU/NEPAD Agency African Biosafety Network of Expertise (ABNE); African Agricultural Technology Foundation (AATF); International Service for Acquisition of Agri-biotech Applications (ISAAA); and African Biotechnology Stakeholders’ Forum (ABSF).